Cohesion between pulmonary artery and bronchus after immune checkpoint inhibitor therapy in a lung cancer patient. Issue 12 (16th October 2020) - Takamori, Shinkichi; Takenoyama, Mitsuhiro; Matsubara, Taichi; Fujishita, Takatoshi; Ito, Kensaku; Yamaguchi, Masafumi; Toyozawa, Ryo; Seto, Takashi; Okamoto, Tatsuro
Abstract : Immunotherapy targeting programmed death‐1 or programmed death‐ligand 1 has become the standard of care for advanced non‐small cell lung cancer (NSCLC). Several recent clinical trials have investigated the efficacy of immune checkpoint inhibitors (ICIs) as neoadjuvant treatment for early NSCLC. However, the safety and feasibility of pulmonary resection after ICIs remain unclear. We herein report a patient in whom cohesion between the left main pulmonary artery and left upper bronchus was found during left upper lobectomy following neoadjuvant ICI combined with chemotherapy. After both central and peripheral sides of the left main pulmonary artery were clamped with the aim of controlling hemorrhage in case of vascular injury, the left main pulmonary artery and left upper bronchus were divided and individually cut with staplers. The thoracoscopic procedure was otherwise uneventful. The patient was discharged from our hospital with no postoperative complications. Thoracic surgeons should anticipate the possible need for management of cohesion between a pulmonary artery and bronchus in patients who have received immune checkpoint inhibitors preoperatively. Abstract : We herein report a patient in whom cohesion between the left main pulmonary artery and left upper bronchus was found during left upper lobectomy following neoadjuvant immune checkpoint inhibitor combined with chemotherapy. The left main pulmonary artery and left upper bronchus were successfully divided and individually cut with staplers. Thoracic surgeons should anticipate the possible need for management of cohesion between a pulmonary artery and bronchus in patients who have received immune checkpoint inhibitors preoperatively.